PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN BERBASIS WEB TERHADAP HASIL BELAJAR MELALUI PENINGKATAN KOMPETENSI GURU GURU SEKOLAH DASAR - Nurhayati, Reni (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2024)
The purpose of this study is to determine the effect of web-based learning media on learning outcomes through increasing the competence of elementary school teachers. Data collection was carried out by survey method using a Likert scale questionnaire. The sampling technique used purposive sampling technique. This study used a quantitative method with a Partial Least Square (PLS) approach using SmartPLS version 3.0 software as a data analysis technique. Based on the research analysis, the results obtained can be concluded that the use of web learning media has a significant impact on increasing teacher competence (P Value = 0.001), teacher competency has a positive and significant impact on student learning outcomes (P Value = 0.000), the use of web media on learning outcomes through teacher competence have a positive and significant impact (P Value = 0.001).